Penggunaan Layanan Bimbingan Kelompok untuk Meningkatkan Tanggung jawab Mengikuti Kegiatan Belajar Mengajar pada Peserta Didik Kelas VIII - Sri Sumarni (Universitas Pancasakti Tegal, 2018)
This research aimed to understand the enhancing of student’s commitment in teaching learning by group guiding in eight grades F of Junior High School 1 Kramat year 2017/2018. Research method used classroom action research with service group guidance object, it had been done in two cycles, consisted of four steps, they were planning, acting, observing and reflecting. Research subject were student of eight grade F of Junior High School 1 Kramat year 2017/2018. The result showed that group guiding could enhance student’s commitment in participating teaching learning, so that this could be used to be alternative model of counseling guidance services